Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ma14112924
|View full text |Cite
|
Sign up to set email alerts
|

Charpy Impact Behavior of a Novel Stainless Steel Powder Wire Mesh Composite Porous Plate

Abstract: A novel powder wire mesh composite porous plate (PWMCPP) was fabricated with 304 stainless steel powders and wire mesh as raw materials by vacuum solid-state sintering process using self-developed composite rolling mill of powder and wire mesh. The effects of different mesh volume fractions, mesh diameters, and sintering temperatures on the pore structure and Charpy impact properties of PWMCPPs were studied. The results show that PWMCPPs have different shapes and sizes of micropores. Impact toughness of PWMCPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Our previous work [ 34 ] demonstrated that the PWMCPP has good impact toughness. Therefore, it is very important to test the uniaxial tensile properties of PWMCPPs to fully research the mechanical properties.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work [ 34 ] demonstrated that the PWMCPP has good impact toughness. Therefore, it is very important to test the uniaxial tensile properties of PWMCPPs to fully research the mechanical properties.…”
Section: Methodsmentioning
confidence: 99%
“…The load and deformation readings were automatically recorded until the sample ruptured. The specimen's total surface area, compressive strength and modulus were calculated using a formula adopted by Li and Zhou (2021) (2)…”
Section: Determination Of Biomechanical and Physical Properties Of Bi...mentioning
confidence: 99%
“…The impact test was carried out using a Charpy impact testing machine with a capacity of 150J/300J and 2 Joules of minimum value of scale graduation (Avery-Denison, model No: 6705U/33122, Leeds, LS102DE England). The specimens were then subjected to a machining process according to the ASTM E23 testing procedure, with a specimen size of 55 X 10 X 10 mm with a notch angle of 45, 2 mm depth and 0.25 mm radius along the base, as shown in Figure 1 (Li and Zhou 2021). The impact strength values were considered the initiation fracture toughness (IS), and the plane strain fracture toughness (FT) was calculated from the expression in Eqn.…”
Section: Determination Of Biomechanical and Physical Properties Of Bi...mentioning
confidence: 99%
“…In our previous work 49,50) we reported on manufacturing porous strip by horizontal rolling process that required wire mesh aperture to be smaller than powder size , thus powder could not fall out of mesh due to gravity, and porous strip was composed of powder-wire mesh structure. Differently, vertical rolling process was used in this work, particle size was smaller than wire mesh aperture so that powder could be pen-etrated into the other side of wire mesh by extrusion pressure, then the unique characteristic of powder-wire mesh-powder sandwich structure was obtained for improving the proportion of powder.…”
Section: Preparation Microstructure and Impact Properties Of A Novel ...mentioning
confidence: 99%